1997
DOI: 10.1007/s004140050030
|View full text |Cite
|
Sign up to set email alerts
|

Radial alveolar count as a tool for the estimation of fetal age

Abstract: A total of 53 normal fetuses with a gestational age ranging from 15 up to 39 weeks was investigated and the radial alveolar count (RAC) was estimated as a parameter for lung maturation. Values lower than 2.0 could only be found in lungs of fetuses aged less than 18 weeks. Between 18 and 25 weeks of gestation, relatively constant levels of RAC were observed but with considerable interindividual variation. In fetuses with a gestational age of more than 25 and especially 30 weeks, a slight or rapid increase in RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…The mean value for RAC is taken as a measure of lung maturation. They found an increase of the mean RAC in relation to gestational age, which has also been confirmed by other studies 61,62 . Askenazi and Perlman 19 used a modification of the method of Emery and Mithal, meaning that they counted the alveolar septi instead of alveoli (RAC alveolar septal count 2 1).…”
Section: Morphometric Radial Alveolar Countsupporting
confidence: 84%
“…The mean value for RAC is taken as a measure of lung maturation. They found an increase of the mean RAC in relation to gestational age, which has also been confirmed by other studies 61,62 . Askenazi and Perlman 19 used a modification of the method of Emery and Mithal, meaning that they counted the alveolar septi instead of alveoli (RAC alveolar septal count 2 1).…”
Section: Morphometric Radial Alveolar Countsupporting
confidence: 84%
“…Reduced RAC and increased L m are potential indications of immaturity of the lung tissue at an age where the lung should have fully mature alveoli. 50,51 The magnitude of the observed changes is consistent with previously reported values from lung diseases, like BPD and chronic obstructive pulmonary disease, and animal models of disease. 52,53 Altered pressure-volume curves and increased compliance in Col6a1 À/À mice (Figure 3) support the finding of simplified parenchymal structure and obstructive lung disease, hallmark pathologic and functional findings in chronic and developmental lung diseases, including BPD.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, RAC has been reported to correlate well with gestational age (14). In the present study, we used lung-to-body weight ratio to diagnose pulmonary hypoplasia, and found that regardless of pulmonary hypoplasia, there was a strong correlation between RAC and gestational age.…”
Section: Discussionsupporting
confidence: 52%